Proceedings of the Fifth International Seminar on English Language and Teaching (ISELT 2017) 2017
DOI: 10.2991/iselt-17.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Reflection on Action: The Use of Reflective Journal Plus Video Recording

Abstract: Abstract-This article discusses a partial result of a study conducted to look at the implementation of reflective teaching to improve student-teachers' pedagogic competence in Micro Teaching Class and Teaching Practicum subject. The focus of this report is to describe the use of reflective journals plus video recording as tools used by the prospective teachers for reflective teaching. Thus, the emphasis will be on the extent to which the combination of these tools helps the student-teachers improve their teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
5
0
3
Order By: Relevance
“…First, it confirms Farrell's (2013) view of journal writing, pointing that writing journal entries allow teachers to practice self-reflection at their own preferred pace. Second, journal writing can benefit student teachers in going deeper into their teaching practices leading to their increased understanding of their teaching skills, as reported by Tiarina and Rozimela (2017).…”
Section: English Teachers' Perceptions Through Closed-ended Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it confirms Farrell's (2013) view of journal writing, pointing that writing journal entries allow teachers to practice self-reflection at their own preferred pace. Second, journal writing can benefit student teachers in going deeper into their teaching practices leading to their increased understanding of their teaching skills, as reported by Tiarina and Rozimela (2017).…”
Section: English Teachers' Perceptions Through Closed-ended Questionsmentioning
confidence: 99%
“…All findings revealed earlier correspond to the framework of reflection for action which Farrell (2013) defines as teachers' reflection on their past teaching experiences to investigate any issues they face. It further implies that all student teachers might expect that reflective practice using video recording in peer teaching would equip them to be independent problem-solvers (Rozimela & Tiarina, 2018;Tiarina & Rozimela, 2017) and independent decision makers (Cirocki & Widodo, 2019).…”
Section: English Teachers' Perceptions Through Closed-ended Questionsmentioning
confidence: 99%
“…Menurut Richards (1992) terdapat macam-macam cara yang dilakukan guru untuk melakukan refleksi diri, diantaranya: (1) membuat catatan pengalaman, (2) laporan diri, (3) autobiografi, (4) jurnal, (5) buku harian dan (6) merekam kegitan pembelajaran. Penelitian telah mengungkap bahwa berbagai teknik reflektif tersebut dapat meningkatkan kualitas pembelajaran yang dilakukan guru di dalam kelas (Göker, 2016;Dieker & Monda-Amaya, 1995;Helyer, 2015;Tiarina & Rozimela, 2017). Melalui proses refleksi, guru berpikir tentang praktik kelas mereka dan mempertanyakan mengapa ada beberapa pelajaran yang sukses dan mengapa ada beberapa yang tidak.…”
Section: Pendahuluanunclassified
“…Selain itu, ada beberapa masalah lagi yang terkait dengan refleksi karena banyak guru tidak melakukan kegiatan refleksi ini sebagai bagian dari rutinitas pekerjaan mereka, karena tidak memiliki waktu atau kesempatan untuk mengembangkan keterampilan refleksi ini. Meskipun demikian, hasil penelitian ini sejalan dengan penelitian sebelumnya bahwa kegiatan reflektif dapat meningkatkan kualitas pembelajaran yang dilakukan guru di dalam kelas (Göker, 2016;Dieker & Monda-Amaya, 1995;Helyer, 2015;Tiarina & Rozimela, 2017)…”
Section: Kelebihan Dan Kelemahaman Pembelajaran Yang Diungkap Melalui Refleksi Diriunclassified
“…The analysis of the world experience has shown that mostly teachers use video blogs to upload tasks for specific lessons (Rakhmanina & Kusumaningrum, 2017). Other teachers assigned their students to film videos about their education process, upload on the blog, and then PEOPLE: International Journal of Social Sciences ISSN 2454-5899 write in a special journal comments on their own video and on other students' videos (Tiarina & Rozimela, 2017).…”
Section: At the National Technical University Of Ukraine "Igor Sikorsky Kyiv Polytechnicmentioning
confidence: 99%